2021
DOI: 10.1080/15363759.2020.1852133
|View full text |Cite
|
Sign up to set email alerts
|

Building Community in an Online Doctoral Program

Abstract: Despite an increasing number of individuals completing doctoral degrees from earlier years, approximately 50% of students who begin a program never complete their degree. Attrition rates for students enrolled in online doctoral programs are higher than students who attend courses in a face-to-face setting. Research has identified that the lack of social integration is one of the key components associated with high student attrition rates in doctoral programs. Creating and maintaining positive student-faculty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Online doctoral programs have garnered heightened interest and acceptance because they offer professional students flexibility, access, cost-effectiveness, and technology-based interactions. Students can examine course materials and participate in learning activities flexibly (Akojie et al, 2019;Bolliger & Halupa, 2012) while being able to balance professional and personal responsibilities (Lee et al, 2020;Studebaker & Curtis, 2021). In terms of access, online doctoral programs remove geographic constraints as a limiting factor as students can participate from anywhere without the need for relocation (Henrikson et al, 2014;Scarpena, 2016).…”
Section: Online Doctoral Programsmentioning
confidence: 99%
“…Online doctoral programs have garnered heightened interest and acceptance because they offer professional students flexibility, access, cost-effectiveness, and technology-based interactions. Students can examine course materials and participate in learning activities flexibly (Akojie et al, 2019;Bolliger & Halupa, 2012) while being able to balance professional and personal responsibilities (Lee et al, 2020;Studebaker & Curtis, 2021). In terms of access, online doctoral programs remove geographic constraints as a limiting factor as students can participate from anywhere without the need for relocation (Henrikson et al, 2014;Scarpena, 2016).…”
Section: Online Doctoral Programsmentioning
confidence: 99%
“…On the other hand, students highly appreciate having a community of peers (Andrew, 2012) and think it contributes decisively to their adjustment and success in the program (Lee, 2020;Studebaker & Curtis, 2021). Having a strong community is closely related to engagement and thus persistence (Byrd, 2016), and it is a protective factor when intentions to drop out arise.…”
Section: Analytical Theme 2: Relational Factorsmentioning
confidence: 99%
“…Reliance on peers helps students alleviate isolation and develop coping mechanisms to face challenges during their doctoral studies (Halter et al, 2006). In this sense, having a cohort with which students experience the same milestones at the same time gives them a sense of security and consistency, in what they describe as a "family-like" sentiment (Byrd, 2016;Studebaker & Curtis, 2021). In-person contact at some point during the PhD program, in the form of initial residencies or sporadic face-to-face meetings, markedly helps build this togetherness, igniting communitybuilding (Berg, 2016;Byrd, 2016;Halter et al, 2006).…”
Section: Analytical Theme 2: Relational Factorsmentioning
confidence: 99%
“…Table 1 below provides a sampling of care acts that EdD faculty members can employ to demonstrate caring ethics for their students. This sample of care acts was influenced by several sources including: (a) Noddings' (1984Noddings' ( /2003 work as discussed in the prior section; (b) Knowles' (1988) theory of andragogy, which posits, in part, that adult learning should be meaningful and relevant, self-directed, and connected to adults' personal and professional lives; (c) research on doctoral student attrition that demonstrates the importance of connection and building relationships among students, peers, and faculty (e.g., Fiore et al, 2019;Hill & Conceição, 2020;Studebaker & Curtis, 2021), and (d) research on and first-hand accounts of EdD students' experiences during the pandemic (e.g., Brochu et al, 2021;Browning, 2021;Bukko & Dhesi, 2021).…”
Section: Employing An Ethic Of Care In Edd Educationmentioning
confidence: 99%
“…Although the specific care acts employed may look different depending on program delivery format, course, and instructor personalities and pedagogies, being aware of students' needs, acknowledging them, and allowing space for caring acts is necessary, impactful, and equity-minded. Studies have shown that building and sustaining relationships among students and between the student and faculty members in doctoral programs supports program completion (Council of Graduate Schools, 2022; Deshpande et al, 2016;Hill & Conceição, 2020), especially in online programs (Fiore et al, 2019;Studebaker & Curtis, 2021). Studentfaculty relationships may be even more critical post-coursework when faculty members take on a supervisory role, but these relationships may also be harder to establish and maintain in online EdD programs (Bawa, 2016).…”
Section: Personal Lifementioning
confidence: 99%